2007
DOI: 10.1063/1.2767225
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Casimir force using aerogels

Abstract: By using silicon oxide based aerogels we show numerically that the Casimir force can be reduced several orders of magnitude, making its effect negligible in nanodevices. This decrease in the Casimir force is also present even when the aerogels are deposited on metallic substrates. To calculate the Casimir force we model the dielectric function of silicon oxide aerogels using an effective medium dielectric function such as the Clausius-Mossotti approximation. The results show that both the porosity of the aerog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…However, an important relation between the three diagonal components of the pressure tensor and the internal energy of the quantum gas systems confined in a rectangular box, P x + P y + P z = 2U/V , can be directly proven from Eqs. (4) and (5). It can be seen from Eq.…”
Section: Thermodynamic Properties Of Confined Quantum Gasesmentioning
confidence: 92%
“…However, an important relation between the three diagonal components of the pressure tensor and the internal energy of the quantum gas systems confined in a rectangular box, P x + P y + P z = 2U/V , can be directly proven from Eqs. (4) and (5). It can be seen from Eq.…”
Section: Thermodynamic Properties Of Confined Quantum Gasesmentioning
confidence: 92%
“…This approach was used for studying the reduction in the Casimir force for porous dielectrics. 38 This approximation has been used for explaining the optical properties of VO 2 near the metal-insulator transition. 39 In this model, the effective value of = eff ͑͒ is determined by the concentration f͑0 Յ f Յ 1͒ of the metal phase following the equation,…”
Section: Composite Media and The Intermediate Region For Metal-imentioning
confidence: 99%
“…We can compare the vdW and Casimir effects with capillary effects. The vdW torque and Casimir torque expressed by normalized tilting angle can be derived as [11], respectively,…”
Section: Static Instability Caused By Capillary Torquementioning
confidence: 99%
“…And they always exist between two objects close to each other. The influence of vdW and Casimir forces on the stability of the MEMS and NEMS actuators with suspended structures has been extensively reported in many literatures [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Chan et al [10] showed that Casimir force can be used to actuate the NEMS devices under certain condition.…”
Section: Introductionmentioning
confidence: 99%